PENGARUH KREDIBILITAS CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIANDAN KEPUASAN KONSUMEN YOU-C 1000 VITAMIN CDI KOTA PEKANBARU - Pakpahan, Eryck Simon Bolivar; Restuti, Sri; Musfar, Tengku Firli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The Celebrity Endorsement is a marketing strategy that makes a product differentiable in this competitive era.Celebrity endorsement is very useful advertising cue to attract or to make more customers and also helpful to attain potential customers attention towards the product or service. Companies use this strategy for brand recognition. The main purpose of the study was to measure the Impact Of Celebrity Endorser Credibility On Purchasing Decision and Costumer Satisfaction You-C 1000 Vitamin C In Pekanbaru. The population in this study is the television viewer in Pekanbaru with a total sample of 96 respondents. Independent variables were the Endorser Credibility, while the Purchasing Decision and Costumer Satisfaction was the dependent variable. Analysis of data using path analysis with SPSS version 20.0.The results showed that the Endorser Credibility significantly influence Purchasing Decision. Endorser credibility significantly influence Costumer Satisfaction. Purchasing Decision significantly influence Costumer Satisfaction You-C 1000 Vitamin C in Pekanbaru.This means, that the endorser credibility has been successfuly make costumer to making decision to purchase the product, and the costumer satisfaction at category satisfied.Keywords: CelebrityEndorserCredibility, Purchasing Decision, Customer Satisfaction.